Graphical Password for Authentication - Patil, Nirmal; Patil, Gaurav; Patil, Swapnil; Jadhav, Chaitali; Durugkar, Santosh (International Journal of Computer Sciences and Engineering, 2014)
The main issues of knowledge-based authentication, generally text-based passwords, are well identified. A Password authentication system is a need of any application or any web service. Password authentication system is responsible for authentication of user for making entrance into a system. Users tend to choose memorable passwords that are easy for attackers to guess, but strong system assigned passwords are difficult for users to remember. So that a password authentication should be stronger as compare to current authentication system. We are proposing a graphical password authentication system instead of only text authentication. Whole system is developed using PCCP (Persuasive Cued Click Point) technique. We use persuasion to influence user choice is used in click-based graphical passwords, encouraging users to select more random click-points. Using this application system becomes totally secured because it uses various samples of images for authentication. By selecting points of various images as a password we can provide maximum security for authentication. Attackers will not able to attack on a system which uses this system because of only strong authentication.